THE PSYCHOLOGICAL FEATURES OF MODERN STUDENTS’ PROFESSIONAL READING DURING SELF-EDUCATION - Martyniuk, Iryna (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the empirical study on the psychological features of modern students’ professional reading, which was carried out in the context of the problem of students’ self-education and their readiness for it. The respondents’ answers to closed, half-open and open questions for the author’s questionnaires “My self-educational work”, “Experimental situations”, “I cognize my profession” were analyzed. These questions were about: 1) doing self-educational work and its vector (whether it is related to the acquired profession or not); 2) regularity of self-educational work; 3) a place of self-educational reading in self-educational work; 4) readiness to self-educational reading in situations of professional need; 5) the results of professional reading; 6) the desire and ability to read scientific, professional literature; 7) understanding of the value of professional reading for professional work. We determined that students’ self-educational work was used for different purposes: to deeper and wider knowledge on various aspects of the acquired profession; to obtain knowledge in other areas not directly connected with the profession. An important part of students’ self-education is corresponding reading. Internet information was used as a reading source in the most cases. Books also were widely used. Many students resorted to other types of activities helping them in their self-education – participation in trainings, master classes, watching videos, ets. However, not all students (regardless of their academic year) were ready to resort to self-educational reading when they needed certain knowledge for practical work. Not all students expressed a desire to read large volumes of information and were able to process them, understand the personal significance of self-educational reading and the importance of working with professional literature. The following psychological features of reading as the way of modern students’ self-education were determined: focus on Internet resources; worsened understanding of the importance of professional literature for practice; searching for short information in professional literature; the understanding of reading importance to gain professional knowledge, but searches for alternative ways to obtain information; irregular self-educational reading of professional literature, reduced understanding of the personal significance of such activities; reduced desire and worsened ability to process large amount of textual information and bad readiness to use reading for practical needs. The general recommendations to accustom modern students to systematic, professional, self-educational reading are presented.